The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1074/jbc.m005610200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Conserved α-Subunit Segment709GDGVND for Mg2+ Binding, Phosphorylation, and Energy Transduction in Na,K-ATPase

Abstract: The segment 708 TGDGVNDSPALKK 720 in the ␣-subunit P domain of Na,K-ATPase is highly conserved among cation pumps, but little is known about its role in binding of Mg 2؉ 710 3 Ala mutation also interferes with transmission of structural changes to the ouabain site and reduces the affinity for binding of Tl ؉ 2-to 3-fold, suggesting a role in transmission of K ؉ stimulation of phospho-enzyme hydrolysis from transmembrane segment 5 to the P domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 29 publications
7
76
0
2
Order By: Relevance
“…The 438 GEAT 441 segment is a part of the nucleotide-binding region of Ca 2ϩ -ATPase and was shown to be in direct proximity to bound ATP (20). Furthermore, even in the E2 state His-1069 is only 18Å away from the Asp residues of the GDGVND motif that are known to be close to the ␤␥-phosphates of the ATP-magnesium complex during catalysis (21). DISCUSSION WNDP has a central role in human copper homeostasis; however, the molecular mechanism of the WNDP-mediated copper transport remains poorly understood.…”
Section: His-1069 Is Not Essential For Phosphorylation Of Wndp By Inomentioning
confidence: 99%
“…The 438 GEAT 441 segment is a part of the nucleotide-binding region of Ca 2ϩ -ATPase and was shown to be in direct proximity to bound ATP (20). Furthermore, even in the E2 state His-1069 is only 18Å away from the Asp residues of the GDGVND motif that are known to be close to the ␤␥-phosphates of the ATP-magnesium complex during catalysis (21). DISCUSSION WNDP has a central role in human copper homeostasis; however, the molecular mechanism of the WNDP-mediated copper transport remains poorly understood.…”
Section: His-1069 Is Not Essential For Phosphorylation Of Wndp By Inomentioning
confidence: 99%
“…Asp-351). Analogous mutational analysis of the Na ϩ K ϩ -ATPase (14) indicates that electrostatic interactions around the phosphorylation site may play an important role in substrate positioning and utilization. We considered that their mutation may alter direct interactions with the nucleotide terminal phosphate or ligation of Mg 2ϩ in conjunction with oxygen atoms of the ATP-terminal phosphate.…”
Section: The Ca 2ϩ Atpase Atp Sitementioning
confidence: 99%
“…Thus, it is highly desirable to investigate the predicted roles of specific residues by mutational analysis. As one relevant example, mutations of residues in the conserved 708 TGDGVNDS sequence in the P domain have already shown that Asp 710 is a Mg 2ϩ binding residue (21). We describe here expression of Na ϩ ,K ϩ -ATPase in the methylotrophic yeast Pichia pastoris and analysis of the wild type protein and the D369N mutant by Fe 2ϩ -catalyzed oxidative cleavages.…”
mentioning
confidence: 99%
“…Thus, expression of functional Na ϩ ,K ϩ -ATPase in P. pastoris at significant levels appeared to be an attractive possibility. Na ϩ ,K ϩ -ATPase has been expressed in many cell types, and used extensively for structure-function analysis, but of most relevance to the present work wild type and mutant Na ϩ ,K ϩ -ATPase proteins have been expressed in Saccharomyces cerevisae and interactions of the pump ligands, ATP, Na ϩ , K ϩ , Mg 2ϩ , and ouabain characterized in detail, particularly by direct binding assays (21,(25)(26)(27)(28)(29). On the other hand, analysis of structural organization and conformational changes by proteolytic cleavage or metalcatalyzed oxidative cleavage has not been described.…”
mentioning
confidence: 99%